2017
DOI: 10.20473/jn.v7i2.4011
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Patients at Pediatric Emergency Services Soetomo Hospital Surabaya

Abstract: Introduction: Installation service system at the Emergency Department (ED) Soetomo Hospital is a coordinated and integrated system under one roof. Include emergency medical and emergency surgery in a very important component of health services at each hospital. The information published on the patient profile and the usefulness of emergency care services indeveloping countries and developed countries is still very rare. This study aimed to describe the characteristic of patients attending the ED at Soetomo hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In this study, 72 pediatric patients (2.7% of the total) attending the ED at HAM Hospital and eight pediatric patients (1.0%) attending the ED at USU Hospital died. The mortality rate is very close to that found in another study, which reported an overall mortality rate for pediatric patients of approximately 1.7% [3] .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, 72 pediatric patients (2.7% of the total) attending the ED at HAM Hospital and eight pediatric patients (1.0%) attending the ED at USU Hospital died. The mortality rate is very close to that found in another study, which reported an overall mortality rate for pediatric patients of approximately 1.7% [3] .…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the majority of the pediatric patients who visited the ED were male (57.8%). In a study performed in 2011 at Dr. Soetomo Surabaya Hospital in Indonesia, it was found that more male patients than female patients visited the emergency room [3] . This could be explained by the higher population of males than females in Indonesia, with 136 142 501 male residents and 134 923 865 female residents (Indonesian Health Profile 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations